2020
DOI: 10.1002/jor.24706
|View full text |Cite
|
Sign up to set email alerts
|

Image‐based design and 3D‐metal printing of a rat hip implant for use in a clinically representative model of joint replacement

Abstract: The aim of this study was to obtain micro‐computed tomography derived measurements of the rat proximal femur, to create parameterized rat hip implants that could be surgically installed in a clinically representative small animal model of joint replacement. The proximal femoral anatomy of N = 25 rats (male, Sprague‐Dawley, 390‐605 g) was quantified. Key measurements were used to parameterize computer‐aided design models of monoblock rat femoral implants. Linear regression analysis was used to determine if rat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Cementless hemiarthroplasty hip implants made of medical-grade titanium (Ti-6Al-4V) were 3D-printed by a research group at the University of Western Ontario, Canada, using a selective laser melting (SLM) 3D printer (AM‐400; Renishaw) 47 (Fig. 2-A).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cementless hemiarthroplasty hip implants made of medical-grade titanium (Ti-6Al-4V) were 3D-printed by a research group at the University of Western Ontario, Canada, using a selective laser melting (SLM) 3D printer (AM‐400; Renishaw) 47 (Fig. 2-A).…”
Section: Methodsmentioning
confidence: 99%
“…However, this model still lacks the accurate clinical depiction of the periprosthetic joint environment since it does not articulate within a weight-bearing joint, nor does it allow for implant osseointegration 46 . The model described in our current study has a unique ball-in-socket design using 3D-printed, medical-grade titanium (Ti-6Al-4V) implants 47 that replaced the native femoral heads of Sprague-Dawley rats and articulated congruently with their native acetabula 48 . The implant stem sits anatomically within the femoral canal and has a roughened surface to enhance stability and bone ingrowth.…”
mentioning
confidence: 99%
“…13,14 To develop a more effective treatment strategy, it is essential to clarify the basic mechanisms underlying postsurgical pain in the acute phase. There have been some reports of animal models exhibiting JR, [8][9][10][16][17][18] but the authors have made no mention of postsurgical pain. Among them, very few studies [16][17][18] reported on the JR model using rodents, which have been most extensively used for pain research.…”
Section: Introductionmentioning
confidence: 99%
“…There have been some reports of animal models exhibiting JR, [8][9][10][16][17][18] but the authors have made no mention of postsurgical pain. Among them, very few studies [16][17][18] reported on the JR model using rodents, which have been most extensively used for pain research. Therefore, we decided to develop a novel animal model of JR using rats.…”
Section: Introductionmentioning
confidence: 99%